The Fate of Activated Group 2 Innate Lymphoid Cells - Mathä, Laura; Martinez-Gonzalez, Itziar; Steer, Catherine A.; Takei, Fumio (Frontiers in Immunology, 2021)
Group 2 innate lymphoid cells (ILC2s) reside in both mucosal and non-mucosal tissues and play critical roles in the first line of defense against parasites and irritants such as allergens. Upon activation by cytokines released from epithelial and stromal cells during tissue damage or stimulation, ILC2s produce copious amounts of IL-5 and IL-13, leading to type 2 inflammation. Over the past 10 years, ILC2 involvement in a variety of human diseases has been unveiled. However, questions remain as to the fate of ILC2s after activation and how that might impact their role in chronic inflammatory diseases such as asthma and fibrosis. Here, we review studies that have revealed novel properties of post-activation ILC2s including the generation of immunological memory, exhausted-like phenotype, transdifferentiation and activation-induced migration.